AI-Augmented Decision-Making Capability, Dynamic Capability, and SME Performance: The Mediating Role of Strategic Agility among Vietnamese SMEs - Nguyễn Thị Thu Hà; Khamla Phommavong (Oikonomia Review: A Journal of Applied Management, Accounting, and Business Strategy, 2026)
Artificial intelligence (AI) has become a strategic resource that reshapes managerial decision-making by enabling organizations to analyze large volumes of structured and unstructured data, identify emerging market patterns, and improve strategic responsiveness. Although AI adoption among small and medium-sized enterprises (SMEs) continues to accelerate across Southeast Asia, evidence explaining how AI-enabled managerial capability is translated into superior organizational performance remains fragmented, particularly within emerging economies. This study investigates the relationships among AI-augmented decision-making capability, dynamic capability, strategic agility, and SME performance using Vietnamese SMEs as the empirical context. A quantitative explanatory design was employed by surveying 350 SME owners and senior managers representing manufacturing, retail, logistics, information technology, and professional service sectors. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The findings demonstrate that AI-augmented decision-making capability exerts a significant positive influence on both dynamic capability and strategic agility. Dynamic capability enhances strategic agility while simultaneously contributing to organizational performance. Strategic agility emerges as the strongest predictor of SME performance and partially mediates the relationship between AI capability and organizational outcomes. The structural model explains 69.4% of the variance in SME performance, indicating substantial predictive power. These findings suggest that technological investment alone is insufficient to improve firm performance. Organizations derive greater value from AI when digital technologies are integrated with adaptive organizational capabilities, continuous learning, flexible resource reconfiguration, and rapid strategic decision processes. The study extends Dynamic Capability Theory by positioning AI-augmented decision-making capability as an antecedent of organizational agility and provides practical guidance for SME managers and policymakers seeking to strengthen digital competitiveness within emerging economies.